Group occupational therapy and yoga: the caregiver experience - Hinsey, Katie M., author; Schmid, Arlene A., advisor; Atler, Karen E., committee member; Fruhauf, Christine, committee member (Colorado State University. Libraries, 2016)
The purpose of this qualitative study was to examine the experiences of caregivers of people with stroke after participating in a group occupational therapy and yoga intervention (MY-OT). Participants elected to either participate in the 8 week MY-OT intervention or to not attend. Participants completed the Zarit Burden Interview and Positive Aspects of Caring scale retrospectively after the MY-OT intervention. Caregivers also chose to participate in focus groups and individual interviews following the intervention. Qualitative data were analysed using an iterative, coding process to generate larger themes based on caregiver experience. Caregivers who attended the MY-OT intervention saw a 47% decrease in caregiver burden and a 26% increase in positive aspects of caring. Those who did not attend saw a 2% decrease in caregiver burden and a 4% decrease in positive aspects of caring. Five themes were elicited from focus groups and interviews: 1) Changes in daily life; 2) Coping Mechanisms; 3) Learning through observation; 4) Sense of community and 5) Learning new information. Group occupational therapy, focused on self-management, and yoga are effective and beneficial interventions for the caregiver and care recipient together.